Research and Practice of Teacher-Student Competition Training Mode based on "Big Data Application Development" Vocational Skill Competition - Shao, Jianji (International Journal of Social Sciences and Public Administration, 2024)
The purpose of this study is to explore and practice the teacher-student training model based on the vocational skills competition "Big Data Application Development". The article firstly emphasizes the importance of the national attention to vocational education and the reform of related teacher team building to improve the quality of vocational education, and points out the key role of vocational skills competitions in cultivating the professional skills of young teachers. By analyzing the organizational structure and impact of the National Vocational College Skills Competition, it highlights the importance of the competition in leading educational reform and improving the quality of technical and skilled personnel training. The innovation and change of the domestic vocational education model are discussed in depth, with special emphasis on the new ideas provided by the model of teachers and students competing together for education reform. In terms of the implementation path, strategies such as analyzing the types of competitions, dissecting the competition syllabus, customizing the training path, sharing experiences and converting competition results are proposed. Finally, the article summarizes the practical experience of the teacher-student competition model in the cultivation of skilled talents, showing the positive impact of this model on improving teachers' vocational skill level and guiding students' competition ability, as well as its important role in improving the cultivation level of vocational skilled talents.